Towards the Question of the Business Culture: Russian Peculiarities of the Entrepreneurial Practices Formation - Наталья Викторовна Бурчилина (Journal of Economic Sociology, 2010)
The paper is prepared by a HSE student with the help of the survey conducted in April-May 2003 within practicum on economic sociology. The paper provides an attempt to consider the transformation of the business culture from the perspective of the settled cultural grounds. The group of entrepreneurs in the paper means that the partners are not only linked to each other but to the people working in one market and competing with each other. In this sense the subject of the analysis is that how do the competition shape and “close” these circles.